2001
DOI: 10.1051/0004-6361:20010911
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic observations of the δ Scorpii binary during its recent periastron passage

Abstract: Abstract. The bright star δ Sco has been considered a typical B0-type object for many years. Spectra of the star published prior to 1990 showed no evidence of emission, but only of short-term line profile variations attributed to nonradial pulsations. Speckle interferometric observations show that δ Sco is a binary system with a highlyeccentric orbit and a period of ∼10.6 years. Weak emission in the Hα line was detected in its spectrum for the first time during a periastron passage in 1990. Shortly before the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
101
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(116 citation statements)
references
References 24 publications
15
101
0
Order By: Relevance
“…5 and 6. The He 5876Å line is very weak but this is similar to the findings of Miroshnichenko et al (2001). Hβ emission was also found to be rather weak.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…5 and 6. The He 5876Å line is very weak but this is similar to the findings of Miroshnichenko et al (2001). Hβ emission was also found to be rather weak.…”
Section: Resultssupporting
confidence: 85%
“…Spectroscopic observations of δ Sco during its recent periastron passage were done extensively by Miroshnichenko et al (2001) between July 2000 and March 2001. These authors have used their spectroscopic data to refine the orbital elements of δ Sco and also discuss possible mechanisms for the mass loss and line emission from the star.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that companions can influence the circumstellar disks of Be stars in several ways: affecting the global disk oscillations (Oktariani & Okazaki 2009), truncating the outer disk (Carciofi et al 2009), and even extracting material from the central star in eccentric orbits (Miroshnichenko et al 2001;Kervella et al 2008). The latter authors found that the orbital period of the close companion of Achernar (HD 10144) appears similar to the observed pseudo-periodicity of the Be phenomenon, indicating that an interaction between the components at periastron could be triggering the Be episodes.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, as the disk cannot easily change size because of the truncation radius, changes in mass loss from the Be star produce changes in the disk density, which can even become optically thick at IR wavelengths. In this case, the IR magnitudes and the H equivalent width are more related to the disk density than to the disk radius (see, e.g., Miroshnichenko et al 2001). Although there was a gap with no measurements from MJD 47,106 to 48,565 (1987November-1991, the magnitudes in all three bands remained at the same level from near the end of the giant outburst observed with EXOSAT until about MJD 49,000 (1993 January).…”
Section: Optical/ir Observationsmentioning
confidence: 96%